Genesis and distribution of soils in relation to parent material and relief in the Central region of Santa Cruz province - Ferrer, J.A. (2001)
Soil-landscape relationships were studied in the central region of Santa Cruz, southern Argentina, between 49-51°S on the Atlantic coast westward to the international border with Chile. Two different sectors were distinguished. The western area, including the Patagonian Andean Cordillera and piedmont is characterised by strong landscape variations, a udic-xeric humidity regime and Nothofagus woodlands; the eastern area has an arid regime, grassland-shrub steppe and large flat structural plain landscape. As a result of the different landscape-relief features and parent materials, the two areas have different soils associations. The western area is characterised by an Andisol-Mollisol-Entisol sequence, whereas the eastern area has an Ardidisol-Entisol trend. The principal characteristics and properties of the soils are analysed and discussed in relation to variations in the conditions of formation.